Peningkatan Keterampilan Menyeduh Kopi dengan Metode Manual Brewing V60 Bagi Penyandang Tunarungu - A Yuni; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2022)
This problem is motivated by the lack of variety in culinary skills at SLBN 02 kota Padang city given to the deaf, where the culinary skills given are more in making food dishes. Therefore, researchers want to provide new skills that have never been taught in school. The purpose of this research is to prove the application of manual brewing method in brewing coffee using V60 can improve the vocational skills of catering for the deaf. This study uses an experimental method with a single subject research approach, with an A-B-A design and data collection techniques using a checklist instrument. The samples taken were the deaf class XII who attended SLBN 02 kota Padang City, totaling 2 subjects.The results obtained in the analysis under conditions and between conditions had an estimated trend of direction, trend, data trail and changes in level which indicated an increase in the ability to brew coffee with the V60 manual brewing method. At the mean level of the baseline-A1 condition was 7.01% and 4.37%, then the mean level of the intervention condition was 46.87% and 46.28%, at the mean level of the baseline-A2 condition was 77.14% and 75, respectively. 32% . The data overlap in the analysis between conditions, in the baseline-A1 and intervention-1 (B) conditions was 5.26% and 2.6%, the data overlap in the baseline-A2 and intervention-1 (B) conditions was 26.3% and 13.1%. Results Based on data analysis, it is stated that brewing coffee using the manual brewing v60 method can improve vocational skills in deaf people.